Critical discursive perspective on the representations of George Floyd and Derek Chauvin in CNN and Fox News / Tan Ching Ling - Tan , Ching Ling (2024)
The killing of George Floyd, an unarmed civilian African American on May 25, 2020, by Derek Chauvin, a former white Minneapolis police officer who refused to lift his knee off Floyd’s neck shone a spotlight on the longstanding police brutality against African Americans in U.S. and reignited the global Black Lives Matter (BLM) movement which began in 2013. To date, there is a lack of studies that provide in-depth insights, from a linguistic and discursive perspective, into U.S. news media’s portrayal of George Floyd and Derek Chauvin. Hence, this critical discourse study employed the Discourse Historical Approach (DHA) to shed light on how, the left-leaning CNN and the right-leaning Fox News represented the social actors - by looking closely at the use of the five discursive strategies, namely the nomination, predication, argumentation, perspectivization, and intensification and mitigation strategies in the news articles. The selected articles were published between May 25, 2020, and May 25, 2023, and the selection was limited to those centred on the key events following Floyd’s death. The analysis revealed the positive representation of George Floyd in both sets of data. Although both news outlets depicted Chauvin as a disgrace to the U.S. police force, Fox News went on to humanise Chauvin and mitigated his past misconducts. The findings of this study provide further understanding on how the selected partisan U.S. news media influence its readers’ perception of the social actors over the span of three years.